Analysis of Basketball Trainers Views about Coronavirus-19 Phobia - Dr. Yahya Gökhan Yalçın; Havva Demırel; Mehmet Altın (Türk Spor ve Egzersiz Dergisi)
Quantitative research models were used in the study, which aimed to to assess the phobia related to the coronavirus-19 of basketball coaches working in Turkey Basketball Federation (TBF) and registered to Turkey's Basketball Coaches Association (TÜBAD). 21 women, and 216 men, 237 active basketball coaches in total, who are TÜBAD members at various levels by the Turkish Leagues, participated to the study. While the personal information form developed by the researchers was used to obtain demographic information in the study. The homogeneity and variances of the data were tested, Kolmogorov-Smirnov (KS) test was applied, and it was determined that the data showed normal distribution. Independent Samples t Test was used in pair matches and One Way Anova test was used in multiple comparisons. Results were evaluated at 95% confidence interval and p lt;0.05 level. Cronbach's Alpha value for the overall scale was determined as .882. According to the results obtained from the findings of the study, no difference was observed in coranavirus 19 phobia values in terms of gender and coaching levels, while statistically significant differences were found in terms of age variables and the status of basketball trainers to practice a different profession besides coaching (p lt;0.05). It was observed that the differences were not observed in both variables in Somatic, Social, Economic and General Dimensions, but they differed in psychological dimensions and the differences were in favor of lower age groups depending on the age factor. As a result, coronavirus-19 phobia of basketball coaches serving in the Turkey Basketball Federation (TBF) and registered Basketball coach of Turkey's Basketball Coaches Association (TÜBAD) is not related to gender and rank, but young coaches have been determined that most affected group psychologically. Likewise, it was concluded that coaches who did a different profession other than coaching were also adversely affected by the situation and this negative situation might have occurred with the concern of working in multiple groups.